"A picture is worth a thousand words": smoking in multi-unit housing in Israel - Mitchell Zeller (BMC, 2023)
Abstract A brief commentary on the need for policy change by the Israeli government to address the problem of tobacco smoke incursion in multi-unit housing. The commentary also includes a call for enhanced products, programs, and services to help smokers in Israel quit.